Chemopreventive effect of omega-3 polyunsaturated fatty acids and atorvastatin in rats with bladder cancer - Nahla E El-Ashmawy; Eman G Khedr; Hoda A El-Bahrawy; Samar M Al-Tantawy (Tumor Biology)
Bladder cancer remains a huge concern for the medical community because of its incidence and prevalence rates, as well as high percentage of recurrence and progression. Omega-3 polyunsaturated fatty acids and atorvastatin proved anti-inflammatory effects through peroxisome proliferator-activated receptor gamma mechanism. However, their chemopreventive effect still remained to be examined and clarified. In this study, bladder cancer was induced in rats by the chemical carcinogen N-butyl-N-(4-hydroxybutyl)nitrosamine. Omega-3 polyunsaturated fatty acids (docosahexaenoic acid and eicosapentaenoic acid: 2:3 w/w; 1200 mg/kg) and/or atorvastatin (6 mg/kg) were given orally daily to rats for eight consecutive weeks concomitantly with N-butyl-N-(4-hydroxybutyl)nitrosamine and continued for further 4 weeks after cessation of N-butyl-N-(4-hydroxybutyl)nitrosamine administration. The histopathological examination of rat bladder revealed the presence of tumors and the absence of apoptotic bodies in sections from N-butyl-N-(4-hydroxybutyl)nitrosamine group, while tumors were absent and apoptotic bodies were clearly observed in sections from rat groups treated with omega-3 polyunsaturated fatty acids, atorvastatin, or both drugs. The study of the molecular mechanisms illustrated downregulation of COX-2 and P53 (mutant) genes and suppression of transforming growth factor beta-1 and the lipid peroxidation product malondialdehyde in serum of rats of the three treated groups. This chemopreventive effect was confirmed by and associated with lower level of bladder tumor antigen in urine. However, the combined treatment with both drugs exhibited the major protective effect and nearly corrected the dyslipidemia that has been induced by N-butyl-N-(4-hydroxybutyl)nitrosamine. Collectively, omega-3 polyunsaturated fatty acids and atorvastatin, besides having anti-inflammatory properties, proved a chemopreventive effect against bladder cancer, which nominates them to be used as adjuvant therapy with other chemotherapeutics.